Att skildra feta kroppar: Vimmelbokslogik och fet temporalitet i Kristin Roskiftes Alle sammen teller - Warnqvist, Åsa; Österlund, Mia (Tidskrift för litteraturvetenskap, 2021)
Depicting Fat Bodies: Wimmelbook Logic and Fat Temporality in Kristin Roskifte’s Everybody Counts In this article we analyze how fat bodies are written into Kristin Roskifte’s picturebook Alle sammen teller ('Everybody counts', 2018). The book strives to depict a diversity of bodies and unlike contemporary Nordic picturebooks in general, fat bodies are included. Alle sammen teller is a wimmelbook built around the concept of counting people and the book’s form is central to our analysis. The wimmelbook structure entails a reading act where linearity and chronology are broken, creating particular effects in relation to the depiction of fat bodies. Introducing the queer theoretical concept fat temporality in Swedish children’s book research, we analyze how manifestations of fat express temporality in Roskifte’s picturebook. The analysis shows that fat bodies within the wimmelbook logic encompass fat temporality which in turn serves a body positivistic purpose. The book thus goes against traditional notions of fat and time, resulting in a multifaceted depic-tion of fat bodies. However, the stigma of fat prevails in the thin normativity expressed in the depictions of children’s bodies.